Solution Trajectories for a Single-Phase Programmed PWM Inverter - Ayong Hiendro; Syaifurrahman Syaifurrahman; Dedi Triyanto; Junaidi Junaidi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper presents solution trajectories for programmed PWM technique to eliminate specific order harmonics in a single phase inverter. Evolutionary algorithm is applied to determine optimum switching angles in order to elmininate low order harmonics for modulation index: -1 £ M £ +1. An implementation using a DE2-115 Cyclone IVE FPGA device is also reported in this paper. The experimental results show that the technique effectively eliminates the specific harmonics, and offers low harmonic distortions on the inverter output after filtering.